The appearance of homo rivalis: Social preferences and the nature of rent seeking - Benedikt Herrmann; Henrik Orzen (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2008)
While numerous experiments demonstrate how pro-sociality can influence economic decision-making, evidence on explicitly anti-social economic behavior has thus far been limited. In this paper we investigate the importance of spite in experimental rent-seeking contests. Although, as we show, existing evidence of excessive rent-seeking is in theory compatible with fairness considerations, our social preference elicitations reveal that subjects' investments are driven by spite, not fairness or reciprocity. We also observe a striking disconnect between individuals' revealed social preferences in our contest game and in a standard prisoner's dilemma, rejecting the idea that there are consistent pro-social, selfish or anti-social 'types'. Moreover, we find that cooperation and reciprocity rates drop substantially after subjects have been exposed to rent-seeking competition.
Keywords: A13; C9; D0; D72; 330; contests; other-regarding preferences; experiments; Soziale Werte; Kooperation; Rent Seeking; Wettbewerb; Konflikt; Nichtkooperatives Spiel; Test